Emergent Leadership in Children's Cooperative Problem Solving Groups. Issue 3 (3rd July 2017) - Sun, Jingjng; Anderson, Richard C.; Perry, Michelle; Lin, Tzu-Jung
ABSTRACT: Social skills involved in leadership were examined in a problem-solving activity in which 252 Chinese 5th-graders worked in small groups on a spatial-reasoning puzzle. Results showed that students who engaged in peer-managed small-group discussions of stories prior to problem solving produced significantly better solutions and initiated significantly more effective leadership than control students. A mediation analysis suggested that it was because of effective leadership that groups who had experienced discussions achieved better problem solutions.